(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chicken being white meat is superior to red meat for a number of reasons, such as its health benefits due to its low fat and cholesterol content. In the gastrointestinal tracts of chickens, there is a high concentration of complex microbial populations, mostly composed of bacteria but also includes fungus, viruses, bacterial, protozoa and microorganisms. The proposed study was conducted for Isolation and identification of bacteria from the intestine of chicken. For this purpose, ten samples of chicken’s intestine were collected and samples were divided into three experimental groups such as Control, T1 and T2. Each group contained ten specimens. The control group showed less numbers of colonies while T1 and T2 showed high colony count. Proper disinfection was maintained. During the whole trial, the bacterial colonies were counted from the both control and experimental groups T1 and T2 as control was outside while T1 and T2 were kept inside the incubator for 24 hours. T3 demonstrated the highest colony count as compared to T1 and control group. The minimum number of colonies observed on control group samples was 33 x 10 CFU/ml and maximum number of colonies were observed was 330 x 10 CFU/mL in control group. The number of colonies was observed in experimental group 1 was 180 x 10 CFU/mL and maximum number of colonies was 10 CFU/mL. In the experimental group 2 the minimum number 218 x 10 CFU/mL and maximum colonies were 510 x 10 CFU/mL. The data was obtained and subjected to statistical analysis by applying one-way ANOVA that showed highly significant differences as the p- value was found to be equal to 0.01 (p<0.05). Hence, after performing the following experiment, we isolated and identified the different bacterial species from intestine of Gallus gallus domesticus.